Hepcidin regulation in a mouse model of acute hypoxia. (25th April 2018) - Ravasi, Giulia; Pelucchi, Sara; Buoli Comani, Gaia; Greni, Federico; Mariani, Raffaella; Pelloni, Irene; Bombelli, Silvia; Perego, Roberto; Barisani, Donatella; Piperno, Alberto
Abstract: Objective: During hypoxia, hepcidin expression is inhibited to allow iron mobilization to sustain erythropoietic expansion. We analyzed molecular mechanisms underlying hypoxia‐induced hepcidin inhibition in an in vivo model of acute hypoxia. Methods: Mice were kept under normal or hypoxic conditions for 6 hours and 15 hours and treated with α‐PDGF‐BB antibody or PDGF‐BB receptor inhibitor. Blood, liver, spleen, and bone marrow were collected to extract RNA and protein or to quantify EPO and PDGF‐BB. mRNA and protein levels were assessed by RT‐PCR and Western blot. Results: Hepcidin was strongly inhibited at 15 hours, and this downregulation followed erythropoiesis activation and upregulation of several growth factors. PDGF‐BB, erythroferrone, GDF15, and TWSG1 were upregulated by hypoxia in the bone marrow, but not in spleen or liver. Inactivation of PDGF‐BB or its receptor suppressed the hypoxia‐induced hepcidin inhibition. Conclusion: Spleen and liver are not involved in the early stages of hypoxia‐induced hepcidin downregulation. Our data support the role of PDGF‐BB and probably also of erythroferrone in the recruitment of iron for erythropoiesis in the hypoxia setting. The rapid normalization of all the erythroid factors against persistent hepcidin suppression suggests that other signals are involved that should be clarified in future studies.